Karaikal Port Private Limited - Nambissan, S. (SAGE Knowledge. Cases., 2014)
On August 22, 2011, Mr. G.R.K. Reddy, Chairman and Managing Director, Mr. M.L.N Acharyulu, Executive Director of Marine Infrastructure and Mr. Arvind Sagar, President, Corporate Initiatives and Planning of MARG Group, were to meet to discuss the way forward to develop phase IIB of the Karaikal port. Phase I of the port, providing 5.2 million tons per annum (mtpa) capacity, was completed in April 2009. Phase IIA, providing 21 mtpa was originally scheduled for completion by September 2011. As of August 2011, MARG Group was still gathering equity investment to complete the development of phase IIA. Commercial operation of Phase IIA was scheduled for January, 2012. Out of the three planned berths in phase IIA, one was constructed, one was under construction, and the construction on the third was yet to begin. Phase IIB proposed doubling the capacity of phase IIA, with an additional investment of Rs 1,390 cr.